A highly sensitive colorimetric approach based on tris (bipyridine) Ruthenium (II/III) mediator for the enzymatic detection of phenylalanine - Messina, Maria Anna; Maugeri, Ludovica; Forte, Giuseppe; Ruggieri, Martino; Petralia, Salvatore (Frontiers in Chemistry, 2023)
Accurate monitoring of phenylalanine concentration plays a prominent role in the treatment of phenylketonuria (PKU). Herein we present an enzymatic assay based on Phenylalanine Dehydrogenase/NAD+ and tris(bipyridine)Ruthenium(II/III) as colorimetric-mediator for the detection of Phenylalanine concentration. The amount of aminoacid was quantitatively recognized by optical absorption measurements at 452 nm, through the conversion of Ru(byp)33+ to Ru(byp)32+ which is induced by the neoformed NADH. A detection limit of 0.33 µM, a limit of quantification of 1.01 µM and a sensitivity of 36.6 a.u nM-1 were obtained. The proposed method was successfully tested using biological specimen from patient affected by hyperfenilalaninemia. The proposed enzymatic-assay showed a high selectivity, making it a promising alternative for the development of versatile assay for detection of phenylalanine in diluted serums.